Bubble‐Channeling Electrophoresis of Honeycomb‐Like Chitosan Composites. Issue 32 (30th September 2022) - Huang, Bo‐Han; Chen, Li‐Jie; Chiou, Yu‐Jie; Whang, Grace; Luo, Yunkai; Yan, Yichen; Wei, Kung‐Hwa; He, Ximin; Dunn, Bruce; Wu, Pu‐Wei
Abstract: A chitosan composite with a vertical array of pore channels is fabricated via an electrophoretic deposition (EPD) technique. The composite consists of chitosan and polyethylene glycol, as well as nanoparticles of silver oxide and silver. The formation of hydrogen bubbles during EPD renders a localized increase of hydroxyl ions that engenders the precipitation of chitosan. In addition, chemical interactions among the constituents facilitate the establishment of vertical channels occupied by hydrogen bubbles that leads to the unique honeycomb‐like microstructure; a composite with a porosity of 84%, channel diameter of 488 µm, and channel length of 2 mm. The chitosan composite demonstrates an impressive water uptake of 2100% and a two‐stage slow release of silver. In mass transport analysis, both Disperse Red 13 and ZnO powders show a much enhanced transport rate over that of commercial gauze. Due to its excellent structural integrity and channel independence, the chitosan composite is evaluated in a passive suction mode for an adhesive force of 9.8 N (0.56 N cm −2 ). The chitosan composite is flexible and is able to maintain sufficient adhesive force toward objects with different surface curvatures. Abstract : A chitosan composite with a vertical array of pore channels is fabricated via a bubble‐channeling electrophoretic deposition process. This unique honeycomb‐like microstructure demonstrates impressive mass transport behavior over that of commercial gauze. In addition, the chitosan composite shows an adhesive force of 9.8 N (0.56 N cm −2 ) in a passive suction mode and is flexible to accommodate different surface curvatures.